Determination of Rhenium in Tungsten and Molybdenum Ore by ICP-MS with Lefort Aqua Regia Microwave Digestion and 8-hydroxyquinoline Precipitation - Yufang XIAO; Yiping JI; Xiaorong REN; Zhigui CHEN; Xuelin DONG; Qinfeng ZHANG (Yankuang ceshi)
BACKGROUNDRhenium (Re) is a key mineral resource widely used in the aerospace field. As one of the rarest elements in the earth, Re rarely exists as an independent mineral but is dispersed in various sulfide ores. Due to its low content and dispersed distribution, the highly sensitive and accurate quantification of Re (ng/g) in complex ore is one of the challenges of modern geological analysis. In order to solve the problem of incomplete decomposition and the great interference caused by co-dissolution of high abundance matrix elements, the existing “digestion-separation” method using 8-12h for one sample is complicated, time-consuming and labor-intensive. Therefore, the development of a simple, fast and low-cost method is urgently required.OBJECTIVESTo establish an analytical method based on Lefort aqua regia microwave digestion, molybdenum and tungsten precipitation, ICP-mass spectrometry for the determination of rhenium in ore.METHODSLefort aqua regia microwave digestion was used to fully decompose ore, and then the organic precipitator 8-hydroxyquinoline (8-HQ) was used to selectively precipitate high-abundance matrix interference elements molybdenum (Mo) and tungsten (W) in the acid-ammonium acetate buffer system (pH 4.5). The organic precipitator 8-HQ was used to precipitate Mo and W to produce stable hydroxyquinoline molybdenum [MoO2(C9H6ON)2] and tungsten [WO2(C9H6ON)2], thereby removing the high-abundance Mo and W in the digestion solution and reducing the interference of matrix on the quantitative analysis of Re. The relevant parameters of Lefort aqua regia microwave digestion and 8-HQ precipitation were systematically studied, and the digestion and precipitation properties were deeply studied by using national certified reference materials.RESULTSThe key parameters that influence ore digestion including volume of Lefort aqua regia and temperature of microwave digestion, were determined as 2.8mL and 130℃ for step 1 and 150℃ for step 2 separately. The addition amount of 8-HQ was also determined as 0.2mL (3%, w%) by comparing precipitation rates of W, Mo and W-Mo solution (25µg/mL) under different amounts, and results showed that the precipitation rate was greater than 95% in different ore digestion solutions. In the established method, the detection limit of Re was 6.9ng/g, the relative error was 0.71%-6.07%, and the RSD was less than 5%.CONCLUTIONSThe method established in this study can effectively eliminate the interference of matrix elements molybdenum and tungsten on Re quantification without introducing new interference elements. Compared with the existing “digestion-separation” process, the method is simpler and faster (shortened from 8-12h for one sample to approximately 1h) and the method has been successfully applied in molybdenum ore, rhenium molybdenum ore and tungsten-tin bismuth ore. This study proves that interfering instead of target element precipitation is feasible and provides a simple, fast and low-cost method for accurate quantification of Re in complex ore.